The Volcanic Hazards of Jan Mayen Island (North-Atlantic) - Gjerløw, Eirik; Höskuldsson, Ármann; Bartolini, Stefania; Biass, Sebastien; Mossoux, Sophie; Gilbert, Jennie; Pedersen, Rolf Birger; Martí, Joan (Frontiers in Earth Science, 2022)
Hazard assessment of remote volcanic islands provides many challenges compared to other volcanoes and volcanic fields. Here we present the first systematic volcanic hazard assessment of Jan Mayen Island, a remote island located in the North-Atlantic Ocean and home to the northernmost active subaerial volcano in the world (Beerenberg Volcano), and we discuss some of the challenges and characteristics of performing a volcanic hazard assessment of a remote volcanic island. Jan Mayen has had at least five eruptions since its discovery at the start of the 17th century. Its Holocene volcanism is mainly characterized by eruptions with styles ranging from Hawaiian to Strombolian, but also by lava domes and Surtseyan eruptions. Based on field data, remote images, topographic data, past data, and computer simulations, our study evaluates the spatial probability of new vents opening, estimates eruption recurrence rates, simulates various eruption scenarios, and produces hazard maps for the different scenarios. This work shows where the hazards of ash fall, and lava flows are more likely to affect the built infrastructure on Jan Mayen Island. This hazard assessment will assist emergency planning and the determination of future land use on the island.